Time Value Analysis of Money in Investment Decision Making: Discounted Cash Flow (DCF) Vs Monte Carlo Method - Tarigan, Edi Suranta; Mawardi, Wisnu (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Investment feasibility analysis is very important in investing so that the investment can be known as feasible or not to run. In investing there is always a risk, where the risk can affect the feasibility of the investment to be run, therefore in this study the risk will be calculated and the effect on investment feasibility will be seen. This type of research uses a combination research method (mixed methods research), which is research based on a combination. The mixed method can also be called the mixed research method, is a planned, systematic, structured, and measurable effort to utilize together two research methods, namely quantitative and qualitative. The results of the investment feasibility analysis can be carried out by all fields. The results of investment analysis using the discounted cash flow method, Monte Carlo simulation, provide positive value in making investment decisions. The risk obtained from the results of the analysis is that the existing risk can reduce the NPV and IRR value of the investment.